Urgensi Ethical Leadership dalam Mencegah Fraud dan Kecurangan di Organisasi: Analisis Deskriptif Literatur - Humaeriyah, Hani; Khoirul, Asyam Faris; Ibrahim, Hammam Rizky; Khaerani, Salsabila Fauzia; Triana, Feby Rahmania; Setiyani, Shinta; Ambardi, Alda Audia; Zulqisthi, Idzni Fatasya; Alamsyah, Iqbal (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Fraud remains a persistent threat to organizational stability that has proven insufficient to be addressed solely through technical controls, necessitating a behavioral approach. This study aims to analyze the urgency of ethical leadership in preventing fraud through a descriptive literature analysis. The research method used is qualitative with a library research approach, reviewing relevant journal articles published between 2020 and 2025. The results indicate that the urgency of ethical leadership lies in two primary mechanisms: (1) Breaking the chain of "rationalization" within the Fraud Triangle, thereby depriving perpetrators of moral justification for committing fraud ; and (2) Acting as a catalyst for the whistleblowing system by creating psychological safety that encourages employees’ courage to report violations. It is concluded that ethical leadership is a strategic foundation that ensures internal control systems function effectively.